Role of energy guide labels in consumers purchase decision for household electrical appliances - Mahlia, Teuku Meurah Indra; Saidur, Rahman; Yanti, P.A.A.; Masjuki, Haji Hassan (Sila Science, 2011)
Due to the rapid economic growth in the past, the usage of electrical products for the last three decades has increased rapidly in Malaysia. To reduce energy consumption, Malaysian Energy Commission has implemented energy labels for electrical appliances. The purpose of the energy labels is to provide the consumers a guideline to compare the size, features, price and efficiency of the product. Research on consumer understanding and use of the label has been limited. This paper discusses the important aspects in consumers purchasing decision and consumers view on energy labels in Malaysia. The study includes the investigation of familiarity, awareness and understanding of the proposed energy labeling by Malaysian respondents. The study found that 65 of respondent were not familiar with the label, however 78 of respondents were understand the label and 79 of respondents are aware about the labels. The undesirable finding was that the efficiency of the product ranked sixth by the respondents in purchasing electrical products.